Supply Channels for Purebred Chicken Eggs - Dzulqarnain, Andi; Haerunianti, Haerunianti (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2024)
This research aims to analyze the supply channels and selling prices for purebred chicken eggs from South Sulawesi entering the Wameo market in Baubau City, the transportation routes for purebred chicken eggs entering the Wameo market, and the margin between the selling price of intermediary traders and the buying price of Wameo market egg traders. The samples used in this research were 13 brokers of purebred chicken eggs who entered the Wameo market, and all the purebred chicken egg traders in the Wameo market were 40 people, which was carried out by census and analyzed descriptively. The results of the analysis show that 1) Producers supplying purebred chicken eggs entering the Wameo market consist of 4 regions in South Sulawesi, namely Sidrap, Soppeng, Bulukumba, and Pangkep. 2) The distribution route for suppliers of purebred chicken eggs from South Sulawesi entering the Wameo market only uses one seaport route, namely Bajoe – Baubau. 3) The marketing margin for purebred chicken eggs entering the Wameo market for intermediary traders is IDR 2,000 per shelf and for holding traders IDR 5,000 per shelf.